Colección del germoplasma de yuca (Manihot esculenta Crantz) del Perú - Quispe Jacobo, Fredy Enrique; Marcelo Salvador, Mavel; Amao Castilla, Hans (Instituto Nacional de Innovación Agraria, 2021)
678 páginas